Biodegradation of high-molecular-weight polycyclic aromatic hydrocarbons by a novel species of the genus Devosia isolated from the deep-sea region of the Kermadec Trench - Wang, Zefei; Zhao, Shanshan; Chen, Gen; Sun, Shiwei; Liu, Yue; Chen, Haixin; Meng, Liang; Han, Zhuang; Zheng, Daoqiong (Frontiers in Microbiology, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are categorized as persistent organic pollutants due to their high toxicity and environmental persistence. In this study, a deep-sea bacterium, designed Naph2T, was isolated from the sediments of the Kermadec Trench using PAH-enriched cultures. A comparative analysis of Overall Genome Relatedness Indices (OGRI) values between Naph2T and closely related strains within the genus Devosia indicated that the isolate represents a novel species, designated as Devosia polycyclovorans sp. nov. (type strain Naph2T = MCCC 1K09447T). This conclusion is further supported by physiological and biochemical analyses. Naph2T exhibited the ability to degrade high-molecular-weight PAHs such as pyrene and benzo[a]pyrene, a feature not previously reported for any strain within the genus Devosia. The degradation degree of Naph2T for pyrene and benzo[a]pyrene reached 58 and 48% at a concentration of 300 mg/L and 200 mg/L, respectively, in 5 days. Genomic analysis revealed key genes associated with PAH degradation, including aromatic ring-hydroxylating dioxygenase (RHD), nagAa, and downstream gene clusters such as pht, pob, and pca. Comparative genomic studies showed that Naph2T harbors a greater number of PAH degradation genes than other species within the Devosia genus, demonstrate that it may have acquired these capabilities through horizontal gene transfer. Transcriptome data revealed significant upregulation of pcaG and pcaH, which encode enzymes involved in the degradation of 3,4-dihydroxybenzoic acid, a downstream intermediate of polycyclic aromatic hydrocarbon metabolism. These findings not only provide novel insights into the ecological roles of the genus Devosia, but also highlight the potential of this new species for PAH bioremediation applications.